COSMIC RAY INTENSITY VARIATIONS DURING 1965. - Sandstrom,A. E.; Dyring,E.; Ekstrom,L.; Lindgren,S.; Sporre,B. (1966)
The recorders have continued as during the last years by one neutron monitor, two cubical telescopes and six inclined telescopes in Uppsala and Kiruna. Tables and figures give a detailed account of diurnal and semidiurnal variations during 1965. Only one decrease is illustrated in a one-hour diagram. (Author)